Recovery after sevoflurane, isoflurane or propofol anaesthesia combined with remifentanil [Remifentanil bazli sevofluran i̇sofluran veya propofol anestezisi sonrasi derlenme] - (:unkn) unknown (My University, 2002)
The aim of this study was to compare the recovery characteristics and adverse respiratory events during the immediate postextubation period after sevoflurane, isoflurane or propofol anaesthesia combined with remifentanil. Forty-five patients, ASA physical status I-II, aged between 18-45 years, were assigned randomly to receive one of three anaesthetic combinations (n=15). Anaesthesia in group RS (remifentanil-sevoflurane) and RI (remifentanil-isoflurane) was induced with thiopentone 5-7 mg/kg and remifentanil 1 μg/kg IV. Maintenance of anesthesia was provided with remifentanil infusion 0.25 μg/kg/min, 0.5 MAC sevoflurane and isoflurane, 50 % air in O2 in group RS and RI respectively. Anaesthesia in group RP was induced with propofol 2 mg/kg and remifentanil 1 mg/kg IV. Maintenance of anaesthesia was provided with remifentanil infusion 0.25 μg/kg/min and propofol infusion 10 mg/kg/h for five min, 8 mg/kg/h, for the next five min and maintained at a dose of 4 mg/kg/h. Remifentanil infusion rate was either increased or decreased 0.05 μg/kg/min if there was a 20 % increase or decrease in blood pressure and heart rate compared with basal values. Emergence times from discontinuation of anesthesia to tracheal extubation, eye opening, response to Verbal commands, and recovery of cognition were recorded. The data obtained was compared statistically by one-way ANOVA and chisquare tests (p<0.05). Time from discontinuation of anaesthesia to tracheal extubation, eye opening, response to verbal commands and recovery of cognition were comparable among groups. It was concluded that anaesthesia with subhypnotic and equipotent doses of sevoflurane, isoflurane or propofol combined with remifentanil had similar recovery characteristics and the incidence of adverse respiratory events were comparable. We suggest that this kind of anaesthetic combination might be preferred for rhinoplasty and endoscopic sinus surgery.
Keywords: Isoflurane; Propofol recovery; Remifentanil; Sevoflurane